Silent Film as Media Archaeology: On Designing a Master’s Degree Course / Немое кино как медиа-археология: подходы к конструированию магистерского курса - USTYUGOVA VERA V. / УСТЮГОВА В.В. (Наука телевидения)
The article presents a methodological elaboration of a syllabus for a university course. The purpose of the course and this presentation is to offer a new focus for teaching the theory and history of silent film within the framework of New Film History concepts. The article is addressed to the expert community of historians, film critics, media researchers, archivists and future specialists in these fields. As a consequence of its rediscovery, early cinema is today an important construct of historical and film studies knowledge. And early cinema itself, with its non-linear development, forgotten histories of color and “talking” films, and huge screens, requires new historiographical models. The dossier of early cinema pushes to investigate the filming schemes, screen technologies, and aspects of music, noise, and verbal accompaniment, as well as draws attention to the potential of film tape restoration. In addition to the traditional teaching methods including lectures and seminars with discussion of theoretical and historiographical texts, the course engages students in doing research using little-studied written sources and technical artifacts available in archives and museum collections. In the cases of Perm, these include materials deposited at the Perm Museum of Local Lore, the Perm State Archive, and the Perm Cinematheque. Students get acquainted with the latest methods of attribution of film archival documents, celluloid, samples of film equipment and film carriers, the vocabulary of archivists and film historians. As a result, students are introduced to current research practices, new horizons of studying the history of cinema through the prism of technical advances and technological experiments. The course attunes the future specialists to the values of the obsolete, the forgotten, and, thanks to new cultural histories, sets a precedent for a conceptual and practical exercise in identifying the facets of contemporary media.